The construction of English verb “send”: A cognitive linguistics study - Moch. Panji Prabaskoro; Prayudha Prayudha (UAD TEFL International Conference)
This research is entitled “The Construction of English Verb “SEND”: A Cognitive Linguistic Study”. It is based on cognitive linguistic, because with cognitive linguistic it could be seen how exactly the construction of English verb “send” and how the construction could have that construction. The aims of the research are; 1) to analyze the construction of English verb “SEND” as a single verb; and 2) to analyze the Construction of English verb "SEND" as a phrasal verb. The data will be collected by using observation method and noting technique. Then, it will be analyzed by using distributional method with expansion, ellipsis, and immediate constituent division. All data that have been collected and analyzed will then be described by qualitative method. As a result, there would be two main outcome found in this research. First, the construction of English verb “send” in the form of single verb, those are English verb “send” as single verb in intransitive construction, transitive construction and ditransitive construction. Second, the construction of English verb “send” in the form of phrasal verb, those are English verb “send” as phrasal verb in intransitive construction, transitive construction, and ditransitive construction.